Accelerated Production of Brain Organoids Using RNA Transfections and Microfluidics as a Model for Traumatic Brain Injury - Sharma, Aparna; Agrawal, Deepak (Indian Journal of Neurotrauma, 2025)
Traumatic brain injury (TBI) is a leading cause of morbidity and mortality worldwide, with limited effective treatment options. Traditional TBI models using animal systems have provided valuable insights but face limitations due to fundamental differences in brain architecture and physiology between humans and animals. Brain organoids, which closely mimic human brain structure and function, represent a transformative tool for studying TBI pathogenesis and therapeutic interventions. Here, we present a protocol for the accelerated production of brain organoids using RNA transfections and microfluidics. This method enables the cost-effective, high-throughput generation of human-induced pluripotent stem cells in xeno-free conditions, providing a scalable platform for modeling brain injury. Our approach integrates advanced microfluidic device fabrication, optimized cell reprogramming using low-dose RNA transfections, and controlled differentiation into brain organoids. Additionally, we outline various injury modeling techniques, including static mechanical forces, fluid shear stress, and dynamic mechanical injury, to simulate TBI in organoid systems. This innovative platform offers a novel strategy to study TBI pathogenesis, screen therapeutics, and develop personalized treatment approaches.
Keywords: brain organoid; microfluids; modeling injury; RNA transfection; traumatic brain injury